The Development of Linggo Asri Forest Seeds Plant Taxonomy Album as Learning Media of Plant Classification Material - Safitri, Naziah Febri; Retnoningsih, Amin; Purwantoyo, Eling (Journal of Biology Education, 2020)
The success of learning are determined by many factors, one of them is the use of learning media as learning source. The effective learning media which is used in the plant materials is media that use the plants around the students as learning sources. The operation of learning media will be more efficient if it is packed as easy and understandable media for students. This research aims to develop the effective and efficient learning media for applying in the plants material. This research uses Research and Development (RnD) method. The developed product is an album of seeds plants in the Linggo Asri Forest as a learning media. This research purposes to identify the seeds plants species in the Linggo Asri forest and also to analyse the feasibility of the album in the learning process. The proper test was done by material and media expert, teacher and also students of X.MIA SMA N 1 Kajen. The validator assessment showed that the album is proper to be applied in the learning process. The effectiveness test showed that learning process using the album is effective from the high of students’ learning outcome and passing percentage.